Note on Quasi-Numerically Positive Log Canonical Divisors - Shigetaka Fukuda (Journal of Mathematics)
We propose a subconjecture that implies the semiampleness conjecture for quasi-numerically positive log canonical divisors and prove the ampleness in some elementary cases.